2016
DOI: 10.3233/ch-152037
|View full text |Cite
|
Sign up to set email alerts
|

Impact of environment on Red Blood Cell ability to withstand mechanical stress

Abstract: Susceptibility of red blood cells (RBC) to hemolysis under mechanical stress is represented by RBC mechanical fragility (MF), with different types or intensities of stress potentially emphasizing different perturbations of RBC membranes. RBC membrane mechanics were shown to depend on cell environment, with many details not yet understood. Here, stress was applied to RBC using a bead mill with oscillation up to 50 Hz, over durations up to 50 minutes. MF profiles plot percent lysis upon stresses of progressive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…The mechanism behind the lower hemolysis with dextran is not fully understood, but it has been suggested that dextran reduces the effects of shear stress on red blood cells (19,20).…”
Section: Commentmentioning
confidence: 99%
“…The mechanism behind the lower hemolysis with dextran is not fully understood, but it has been suggested that dextran reduces the effects of shear stress on red blood cells (19,20).…”
Section: Commentmentioning
confidence: 99%
“…The mechanical stability of erythrocytes also deserves attention [2628], especially for the analysis of erythrocyte membrane behavior in situations of increased mechanical aggression, which is the main challenge found by red cells in the blood circulation of women with preeclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…Prospect, IL). Mechanical Fragility (MF) testing and profile development was performed using a vertically oscillating bead in a sample and having incremental hemolysis being measured at respective stressing durations, as was described previously [7], except now using custom made cylindrical beads in addition to the standard spherical (ball) beads. Area Under the Curve (AUC), representing the area under the collected fragility profile, is a profile-based value that was used here to evaluate induced hemolysis over a given aggregate stress duration.…”
Section: Methodsmentioning
confidence: 99%
“…protective effect afforded by albumin can be attributed to changes in properties of turbulent flows in the bead's wake [7]. Furthermore, use of a cylindrical (rather than spherical) bead introduces additional stresses, beyond those of the bead's turbulent wake, associated with the bead's annulus (which is notably minimal in the case of a spherical bead).…”
Section: Role Of Bead Weightmentioning
confidence: 99%
See 1 more Smart Citation